Intermediate-depth and shallow core drilling operations in Mizuho Plateau, Antarctica, in 1983-84 field season (abstract) - Narita,Hideki; Nakayama,Yoshiki; Nakawo,Masayoshi; Suzuki,Yosio (1985)
P(論文) departmental bulletin paper